Transitions from intensive eating disorder treatment settings: qualitative investigation of the experiences and needs of adults with anorexia nervosa and their carers. Issue 4 (20th July 2022) - Clark Bryan, Danielle; Macdonald, Pamela; Cardi, Valentina; Rowlands, Katie; Ambwani, Suman; Arcelus, Jon; Bonin, Eva-Maria; Landau, Sabine; Schmidt, Ulrike; Treasure, Janet
Abstract : Background: Relapse rates for individuals with anorexia nervosa after intensive hospital treatment (in-patient or full-time day care) are high. Better knowledge about the difficulties and opportunities that arise during this transition is needed to identify factors that support or hinder continued recovery upon discharge. Aims: The aim of this study was to explore the experiences of adult patients and their chosen carers on the process of transitioning from intensive eating disorder treatment settings to the community. Method: Semi-structured interviews were conducted with patients with anorexia nervosa ( n = 11) discharged from day or in-patient care from specialised eating disorder units across the UK, and their chosen carers ( n = 20). Data were analysed with inductive thematic analysis. Results: Four interrelated themes were identified for both groups. For patients, themes were continuity of care, ambivalence about continued recovery, the value of social support and a call for enhanced transition support. For carers, themes were the impact of the eating disorder on themselves and the family, perceptions of recovery and support post-discharge, the impact of previous treatment and care experiences, and desire to create a supportive transition process. Conclusions: The study provides an insight into the unique challenges that individuals with anorexia nervosa face upon leaving intensive treatment. A lack of post-discharge planning, support system and identity formation outside of anorexia nervosa were perceived as barriers to continued recovery. Patients and carers advocated for transition support that incorporates a phased, inclusive approach with accessible professional and social support in the community.